KRITIK KENYAMANAN BANGUNAN RUMAH KOS DI LOWOKWARU KOTA MALANG - Annisa' Carina; DONNY JULY PRASETYO (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2023)
Malang is a student city, marked by the many universities in Malang, but many boarding houses do not provide comfort to the residents. Comfort which is the focus of research is lighting, ventilation and circulation settings. The method used is descriptive deductive architectural criticism, namely departing from theory to gain substantive knowledge and its parameters. Based on the analysis of comfort, it was found that the area of the lighting opening in room 1 was 2.61m2, and in rooms 2, 3 and 4 it was 1.26m2. This means that the lighting in room 1 meets the standard, while rooms 2, 3 and 4 do not meet the standard. In terms of ventilation, room 1 has a ventilation area of 4.74m2 and rooms 2, 3 and 4 have an ventilation area of 2.04m2. Means that all rooms have met the standard. In terms of human and vehicle circulation, the object has a width of 1m which functions as access for motorbikes from the gate to the parking lot, and the motorbike parking area for the object has a size of 1.5m x 3m for 2 motorbikes, meaning it does not meet the standards.